High temperature thermoelectric properties of highly c-axis oriented Bi2Sr2Co2Oy thin films fabricated by pulsed laser deposition - 陈珊珊 王淑芳 刘富强 闫国英 陈景春 王江龙 于威 傅广生 (中国物理B：英文版, 2012)
High-temperature thermoelectric transport property measurements have been performed on the highly c-axis oriented Bi2Sr2Co20v thin films prepared by pulsed laser deposition on LaA1Oa （001）. Both the electric resistivity p and the seebeck coefficient S of the film exhibit an increasing trend with the temperature from 300 K-1000 K and reach up to 4.8 m. cm and 202 V/K at 980 K, resulting in a power factor of 0.85 mW/mK which are comparable to those of the single crystalline samples. A small polaron hopping conduction can be responsible for the conduction mechanism of the film at high temperature. The results demonstrate that the Bi2Sr2Co2Oy thin film has potential application has high temperature thin film thermoelectric devices,